Information environment and corporate innovation: A survey - Bohui Zhang (Asian Development Bank Institute (ADBI), 2019)
A field of research that attracts increasing attention from scholars is the impact of the information environment on corporate innovation. In this article, I review the research from three points of view in relation to the information environment: (i) managers' voluntary disclosure, (ii) disclosure mandated by regulation, and (iii) information intermediaries (media and analysts). Research suggests that the information environment generally plays both positive and negative roles in corporate innovation by affecting effort and efficiency through different mechanisms. Finally, I put forward some suggestions on two aspects of future research directions of this field.
Keywords: G14; G32; O31; 330; information environments; media coverage; and firm innovation